Green Startup Policy in Vietnam: Current Status and Challenges for Sustainable Development - Danh Thang, Phung (VNU Journal of Science: Policy and Management Studies, 2024)
In the context of globalization and increasing awareness of climate change, green and sustainable economic development has become an inevitable trend for nations worldwide. With a strong commitment to reducing greenhouse gas emissions and achieving the Sustainable Development Goals (SDGs), Vietnam is striving to promote green startup initiatives to maximize economic potential while protecting the environment and natural resources. Policies supporting green startups play a crucial role in creating a favorable environment, fostering creativity and innovation, and enhancing the competitiveness of domestic green enterprises. However, the implementation of these policies in Vietnam still faces many challenges, including an inconsistent legal framework, fragmented support resources, and barriers in accessing capital and markets. This article aims to analyze the current state of green startup support policies in Vietnam and highlight key issues to consider during the policy formulation and implementation process.